Effect of a multimethod quality improvement intervention on antipsychotic medication use among residents of long-term care - Adrian Wagg; Fiona Clement; Heather M Hanson; Tova Léveillé; Mollie Cole; Lesley JJ Soril; James Silvius (BMJ Open Quality)
Background Antipsychotic medications are used to address neuropsychiatric symptoms associated with dementia. Evidence suggests that among older adults with dementia, their harms outweigh their benefits. A quality improvement initiative was conducted to address inappropriate antipsychotic medication use in long-term care (LTC) in the province of Alberta.Methods We conducted a multimethod evaluation of the provincial implementation of the project in 170 LTC sites over a 3-year project period incorporating a quasi-experimental before–after design. Using a three-component intervention of education and audit and feedback delivered in a learning workshop innovation collaborative format, local LTC teams were supported to reduce the number of residents receiving antipsychotic medications in the absence of a documented indication. Project resources were preferentially allocated to supporting sites with the highest baseline antipsychotic medication use. Changes in antipsychotic medication use, associated clinical and economic outcomes, and the effects of the project on LTC staff, physicians, leaders and administrators, and family members of LTC residents were assessed at the conclusion of the implementation phase.Results The province-wide initiative was delivered with a 75% implementation fidelity. Inappropriate antipsychotic medication use declined from 26.8% to 21.1%. The decrease was achieved without unintended consequences in other outcomes including physical restraint use or aggressive behaviours. The project was more expensive but resulted in less inappropriate use of antipsychotics than the pre-project period (incremental cost per inappropriate antipsychotic avoided of $5 678.71). Accounts from family, organisational leaders, and LTC staff were supportive of the project activities and outcomes.Conclusion This quality improvement initiative was successfully delivered across an entire delivery arm of the continuing care sector. Quality of care in LTC was improved.